E-Performance Implementation in Improving Teacher Professionalism and The Effectiveness of Educational Management in Madrasah - Ridwan Andi Mattoliang (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
E-Kinerja is a digital platform developed by the National Civil Service Agency (BKN) to support the recording, monitoring, and evaluation of ASN performance. In education, particularly in madrasas, this system plays a role in improving teacher professionalism, accountability, and the effectiveness of school management. This article discusses the implementation of E-Kinerja, its benefits, and its contribution to madrasah administration and the implementation of the Independent Curriculum. The study results show that E-Kinerja provides accurate and real-time performance data to support decision-making and teacher competency development. However, network limitations, administrative burdens, and technical capabilities are obstacles, requiring improvements in infrastructure and digital literacy.